VALUING INVENTORIES IN PROFIT AND LOSS DETERMINATION. - Lorig, Arthur N. (The Accounting Review, 1943)
Abstract This article focuses on inventory valuation in profit and loss accounting. Some limitations of the proposed change in inventory treatment should be made clear. It is apparent that the process of charging opening inventory to cost of sales at market price and pulling out closing inventory at cost eliminates only those fluctuations in value which properly apply to previous periods. Changes in the market value of goods occurring between either the opening inventory date or the date of purchase and the date of sale are not isolated. They are allowed to affect operating results, since they could not be separated satisfactorily from normal operations for the period. The purpose is to isolate the results of operations for this period. In times like the present, when prices are shifting rather rapidly, the proposed change in inventory accounting would offer its greatest service. The balance sheet would be made to give a truer picture of the current position, and the current ratio would be more significant. Furthermore, the operations for each accounting period would be set forth more nearly divorced from those of other periods. The operating statement would thus become a truer index of current operating efficiency.